Rapid and sensitive detection of superoxide dismutase in serum of the cervical cancer by 4-aminothiophenol-functionalized bimetallic Au-Ag nanoboxs array - Ji Xia; Gao-Yang Chen; Gao-Yang Chen; You You Li; Lu Chen; Dan Lu; Dan Lu (Frontiers in Bioengineering and Biotechnology, 2023)
Early, efficient and sensitive detection of serum markers in cervical cancer is very important for the treatment and prognosis to cervical cancer patients. In this paper, a SERS platform based on surface enhanced Raman scattering technology was proposed to quantitatively detect superoxide dismutase in serum of cervical cancer patients. Au-Ag nanoboxs array was made by oil-water interface self-assembly method as the trapping substrate. The single-layer Au-AgNBs array was verified by SERS for possessing excellent uniformity, selectivity and reproducibility. 4-aminothiophenol (4-ATP) was used as Raman signal molecule, it will be oxidized to dithiol azobenzene under the surface catalytic reaction with the condition of PH = 9 and laser irradiation. The quantitative detection of SOD could be achieved by calculating the change of characteristic peak ratio. When the concentration was from 10 U mL−1–160 U mL−1, the concentration of SOD could be accurately and quantitatively detected in human serum. The whole test was completed within 20 min and the limit of quantitation was 10 U mL−1. In addition, serum samples from the cervical cancer, the cervical intraepithelial neoplasia and healthy people were tested by the platform and the results were consistent with those of ELISA. The platform has great potential as a tool for early clinical screening of cervical cancer in the future.